Impact of social media-supported flipped classroom on English as a foreign language learners’ writing performance and anxiety - Zhao, Xiangfeng; Yang, Yanping (Frontiers in Psychology, 2023)
As flipped classroom has received much attention by researchers and educators, some scholars have investigated the effectiveness of this mode of teaching in English as a foreign language (EFL) contexts. In this research direction, the current research examined the impacts of a flipped writing course on writing development and anxiety of Chinese EFL learners. For this aim, a sample of 50 Chinese EFL learners from two intact classes of a language school were selected as the participants via convenience sampling method. The participants of these two intact classes were randomly assigned to a control group (n = 24), who were taught based on the regular method of writing instruction, and an experimental group (n = 26), who were instructed based on flipped instruction method. Two writing tasks and a writing anxiety inventory were used to gather the data. The results of descriptive and inferential statistics showed that the experimental group who were taught based on flipped writing instruction could significantly enhance their writing performance. Moreover, the writing anxiety of the participants was substantially reduced because of the flipped course. The findings of this quasi-experimental study may have significant implications for EFL research and practice.